PLAGIARISME DETECTION SYSTEM ON THIEF FACULTY OF COMPUTER SCIENCE UNIVERSITY U'BUDIYAH INDONESIA BASED TEXT MINING - TB, Desita Ria Yusian; Fathiah, Fathiah (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2016)
Plagiarism is the act of intentionally or unintentionally in obtaining or trying to obtain credit or value to scientific work., citing part or all of the work / or scientific work of others who are recognized as scientific works, co without stating the source appropriately and adequately. Problem of plagiarism has become a phenomenom that is being discussed in academic forums. Based on a variety of information about the practice of plagiarism is increasingly disturbing, this study conducted at the Ubudiyah University Indonesia (UUI). This system will implemented the detection system plagiarism that will be creating using a document apllied method of vector space model to analyze similarities in document displayed on the web browser. Input on this system is a document in the form of text format whith the extention test performed on real data that is usig data documents with vector space  model algorithm value is above 85% to 100% for high level document. As for a document with a low degree of similarity values below 50%.Keyword : plagiarism, vector space model, similarity